A Review of Emergency Medical Service Rate under a Project of Financial Recommendation for Universal Coverage for Emergency Patients (UCEP) - Chiangchaisakulthai K, Suanrueang P, Wongsin U, Thumvanna P, Sakunphanit T (Journal of The Department of Medical Services, 2020)
Background: Presently, the Fee Schedule is employed to be an emergency medical expenses reimbursement mechanism. However, there is plenty of rooms for improvement. To be able to most effectively improve the reimbursement and the relevant agencies work budget managing. Therefore, to scrutinize and modulate the fee schedule is necessary. Objective: The object of this study (1) To scrutinize the emergency medical services rates classifying by reimbursement. (2) To explore the service rate lists which are not included in the fee schedule and the reimbursement difficulties. Method: A mixed-methods study. Quantitative methods direct using the emergency medical service reimbursement information under a project of financial recommendation for Universal Coverage for Emergency Patients (UCEP). The UCEP data which the infirmary providing emergency medical services submit the National Health Security Office the information in the fiscal year 2017 to reimburse. Qualitative methods directly interview physicians and medical staff organizations to explore the service rate lists which are not included in the fee schedule and the reimbursement difficulties. Result: The result showed that the number of emergency medical expenses disbursement, accounting for 23.18% of all at of the total (9,647 items). The most of charges were higher than the fee schedule rate particularly drugs and parenteral nutrition category which was the highest average reached over 714 times. There were considerably different proportions of charges between the reimbursement rate and the fee schedule rate especially drugs and medical supply groups. Glucose (Blood, Urine, and Other) was the highest charged Item, accounting for over 9,900 times. There were 81,493 times without recording disbursement code and no code 13,843 items. However, 7,692 items were the already list of fee schedules. The difficulties such as 1) in the early stages, there was a disagreement from the lists that were not consistent with the private hospital lists using in their regular services. However, they have adjusted and solved those problems latterly. 2) Some drug lists could not be filled with data details for reimbursement. There was not the coverage of some medical supplies used lists in regular services in the fee schedule. Some artificial organs and medical devices could not specify material used types. Outpatient and inpatient hospital services were not available in the fee schedule. Conclusion: If the Fee Schedule is put on the payroll to be an emergency medical expenses reimbursement mechanism continuously, it will need to have a regular unit developing emergency medical services rates. Additionally, Thai Medicines Terminology (TMT) has to be utilized to national drug codes and medical terminology, and also the Logical Observation Identifiers Names and Codes (LOINC) have to be administered to a universal code system for identifying laboratory and clinical observations.